Pertimbangan Hukum Hakim Terhadap Kesaksian Yang Meringankan Dalam Tindak Pidana Pemerkosaan - Cantika W Muhrim; Sherly Adam; Elias Zadrach Leasa (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The judge's legal considerations are one aspect of realizing the value of a judge's decision that contains justice and contains legal certainty. In deciding a case the judge must consider the juridical, sociological and philosophical truths.Purposes of the Research: Analyze and discuss the judges legal considerations against the mitigating testimony based on the decision of the district cour No. 396/Pid.B/2019/Pn.Amb)”. analyze and discuss the imposition of sanctions against the crime of rapoe based on decision No. 396/Pid.B/2019/Pn.Amb)”. Methods of the Research: This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach.Results of the Research: The results showed that the judge’s leal considerations in the decision No. 396/Pid.B/2019/Pn.Amb resulted in the defendant bein acquitted because of the weak evidence presented by the public prosecutor, namely there were no eye witnesses, expert witnesses and also Visum et Repertum which were not used as evidence. On the other hand, the defendant has a mitigating witness, where mitigating facts greatly influence the judgge in imposing sancsions. Based on this decision the judge that the intercourse was consesual, so the judge handed down an acquittal against the defendant.